Observed Frequency and Clinical Management of Sodium Polystyrene Sul-fonate Treated Hyperkalemia in Patients with Chronic Heart Failure in a Private Center in Costa Rica - Zavaleta Monestel, Esteban (2025)
Introduction: Hyperkalemia is a common complication in patients with heart failure (HF) and is associated with increased mortality, a higher risk of hospitalization, and interruption of evidence-based neurohormonal therapies. In Costa Rica, however, information regarding its frequency, clinical characteristics, and management remains limited. Methods: This observational, descriptive, and retrospective study was conducted at the Heart Failure Clinic of Hospital Clínica Bíblica (San José, Costa Rica) between June 2015 and June 2025. Cases were identified through the institutional dis-pensing registry of sodium polystyrene sulfonate (SPS), allowing capture of episodes specifically treated with this med-ication. Patients with confirmed HF were included, while those with stage V chronic kidney disease (CKD), those on dialysis, and individuals with incomplete medical records were excluded. The observed proportion of SPS-treated hy-perkalemia was estimated using the total number of unique HF patients treated during the same period as the denomi-nator. Demographic data, comorbidities, pharmacologic therapy, hyperkalemia severity, and clinical management were collected. Results: A total of 355 medical records were reviewed, of which 42 corresponded to HF patients who experienced hyperkalemia treated with SPS. Among 11,805 unique HF patients in the institutional database during the study period, the observed proportion was 0.37%, with annual variation between 0.26% and 2.1%. The cohort consisted predominantly of older adults, 74% of whom were aged 80 years or older. Thirty-five patients had CKD (mainly stages 3 and 4), and 21 had diabetes mellitus. Severe hyperkalemia was the most common presentation (61.9%), followed by moderate (28.6%) and mild (9.5%) cases. According to chronic treatment lists, 30 patients were re-ceiving RAAS inhibitors and 21 were receiving MRAs at the time of the episode. Discontinuation of spironolactone was the most frequent therapeutic intervention, while RAAS inhibitors were generally maintained or dose-adjusted. Two deaths occurred during follow-up, both attributed to HF decompensation, with no arrhythmias documented before death. Conclusions: In this private-center registry, the observed proportion of SPS-treated hyperkalemia in HF patients was low, although this reflects methodological constraints and does not represent the true incidence of hyperkalemia. The identified cases occurred in a clinically vulnerable population characterized by advanced age, multimorbidity, and a high prevalence of CKD. The predominance of severe hyperkalemia and frequent MRA discontinuation underscore the challenge of bal-ancing hyperkalemia risk with the need to maintain therapies with established prognostic benefit. These findings high-light the importance of strategies that support continuation of guideline-directed medical therapy and underscore the need for future multicenter studies,i ncluding patients with advanced CKD to better characterize the burden of hyper-kalemia in HF populations in Costa Rica.